Human Resource Collaboration Across Government Agencies to Enhance Public Service Effectiveness: A Multi-Case Qualitative Study in West Kotawaringin Regency, Indonesia (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Public service reform in Indonesia increasingly emphasizes inter-agency collaboration as a mechanism to enhance administrative efficiency, service integration, and responsiveness to citizens’ needs; however, in many regions, including West Kotawaringin Regency, collaborative practices remain fragmented due to uneven human resource (HR) capacities, inconsistencies in standard operating procedures (SOPs), and limited technological integration across institutions. This study aims to examine the current state of HR collaboration, identify key barriers and enabling factors, and propose an integrated and adaptive HR collaboration model to strengthen public service delivery. Using a qualitative multi-case study approach, data were collected through semi-structured interviews with leaders and operational staff from multiple regional government agencies and analyzed using NVivo 15 to generate thematic coding and visual tools such as word clouds, hierarchy charts, and project maps. The findings indicate that current collaboration is largely transactional and administrative, exemplified by the physical co-location of agencies at the Public Service Mall (MPP) without effective systemic interoperability. Three critical themes emerged: gaps in HR distribution, competencies, and role clarity; structural and behavioral constraints including sectoral ego, SOP discrepancies, and limited digital integration; and opportunities to enhance collaboration through shared digital dashboards, inter-agency forums, and cross-functional HR mobility. Based on these results, the study proposes a three-pillar Integrated and Adaptive HR Collaboration Model comprising comprehensive digital integration, flexible HR competency sharing, and inclusive service co-creation involving community stakeholders, offering both theoretical contributions to collaborative governance and practical guidance for regional governments seeking to improve public service effectiveness.